Mutual Regulation of TLR/NLR and CEACAM1 in the Intestinal Microvasculature: Implications for IBD Pathogenesis and Therapy. Issue 2 (5th October 2018) - Schirbel, Anja; Rebert, Nancy; Sadler, Tammy; West, Gail; Rieder, Florian; Wagener, Christoph; Horst, Andrea; Sturm, Andreas; de la Motte, Carol; Fiocchi, Claudio
Abstract: Background: Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1) displays multiple activities, among which pathogen binding and angiogenesis are particularly prominent. These same functions are also exerted by Toll- and NOD-like receptors (TLRs and NLRs), which are critical mediators of innate immune responses. We investigated whether a functional inter-relationship exists between CEACAM1 and TLRs and NLRs and its potential impact on induction of intestinal angiogenesis. Methods: This hypothesis was tested using human intestinal microvascular endothelial cells, a unique cell population exposed to microbial products under physiological and pathological conditions. Results: The results show that activation of TLR2/4, TLR4, NOD1, and NOD2 by specific bacterial ligands selectively and differentially upregulates the levels of cellular and soluble CEACAM1 produced by intestinal microvascular endothelial cells. The results also show that CEACAM1 regulates the migration, transmigration, and tube formation of these endothelial cells and mediates vessel sprouting induced by specific TLR and NLR bacterial ligands. Combined, these results demonstrate a close and reciprocal regulatory interaction between CEACAM1 and bacterial products in mediating multiple functions essential to new vessel formation in the gut mucosa. Conclusions: A coordinated and reciprocal interaction of CEACAM1 and microbiota-derived factors is necessary to optimize angiogenesis in the gut mucosa. This suggests that a coordination of endogenous and exogenous innate immune responses is necessary to promote intestinal angiogenesis under physiological and inflammatory conditions such as inflammatory bowel disease.